1985
DOI: 10.1093/jat/9.2.91
|View full text |Cite
|
Sign up to set email alerts
|

4-Bromo-2,5-dimethoxyphenethylamine: Identification of a New Street Drug

Abstract: The identification of 4-bromo-2,5-dimethoxyphenethylamine as a street drug is described. NMR, UV, and mass spectral data used in the identification of the compound are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…[9]. For some of the substances that belong to the 2C-series, analytical data are available [15][16][17][18][19][20][21][22][23]. Screening for and validated quantification of 2C-E itself in human blood plasma has been published using gas chromatography-mass spectrometry (GC-MS) [24].…”
Section: Introductionmentioning
confidence: 99%
“…[9]. For some of the substances that belong to the 2C-series, analytical data are available [15][16][17][18][19][20][21][22][23]. Screening for and validated quantification of 2C-E itself in human blood plasma has been published using gas chromatography-mass spectrometry (GC-MS) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Among these types of analogues, 2,5-DMA and 4-bromo-2,5-dimethoxyamphetamine (DOB) [1][2][3] were listed in Schedule 1 of the Controlled Substances Act in 1971. 4-Bromo-2,5-dimethoxyphenethylamine (2C-B) [1], which was fi rst synthesized by Alexander Shulgin [4] and appeared on the drug market in the 1980s [5][6][7], is also listed in Schedule 1. In Japan, 2,5-DMA, DOB, and 2C-B are controlled by the Narcotics and Psychotropic Control Law, and 4-iodo-2,5-dimethoxyphenethylamine (2C-I) [8] is controlled only by the Pharmaceutical Affairs Law.…”
Section: Introductionmentioning
confidence: 99%
“…The data concerned is intended to serve for screening, identifi cation, and quantitation of the drugs contained in seized tablets, crystals, and powder; the 1 3 thin-layer chromatography (TLC), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS). To our knowledge, such a comprehensive study has not been reported, although some reports dealing with a single or a few drugs are available [2,3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2C-B was first synthesized in 1974 1) and entered the drug market in the 1980's, 3) but little information is available concerning its metabolic fate. In a previous study, we reported on the identification of six metabolites of 2C-B in the urine of rats had been administrated 2C-B hydrochloride.…”
Section: Introductionmentioning
confidence: 99%